In Vivo Evaluation of the Anti-Skin-Ageing Bioactivity of a Recombinant Dual Humanised Collagen and Poly-L-Lactic Acid - Mingjie Tong; Xin Zhou; Jiongni Zhong; Dengjian Qu; Wei Chen; Chun Chen; Yiting Wang; Yaoping Liu; Shaochuan Li; Yuan Xiao; Ning Wang; Chaowan Guo; et al. (Bioengineering)
This study introduces a novel recombinant humanised collagen (DuCol) developed through codon optimisation and prokaryotic soluble expression, exhibiting exceptional biocompatibility and bioactivity. Structural integrity was confirmed via RP-HPLC, SEM, and CD spectroscopy. In vitro evaluations revealed DuCol’s dose-dependent enhancement of NIH-3T3 fibroblast proliferation, adhesion, and migration. In a D-galactose-induced ageing rat model, subcutaneous implantation of DuCol showcased time-dependent anti-ageing effects. Early-stage intervention (30 days post-injection) markedly upregulated COL1A1 expression through the TGF-β/Smad3 pathway activation, outperforming poly-l-lactic acid (PLLA) in collagen deposition. Histological analysis revealed 23.4% greater dermal thickness in DuCol-treated groups compared to PLLA at 90 days. While PLLA exhibited sustained collagen stimulation beyond 90 days, DuCol exhibited superior early-phase efficacy (p < 0.001) with comparable safety profiles (no inflammatory response observed through 180-day monitoring). The combinatorial PLLA/DuCol (P&C) formulation synergistically enhanced dermal regeneration, achieving a 31.7% thicker collagen matrix than monotherapy groups. These results underscore the potential of DuCol as a novel implantable filler material for skin repair and regeneration.